(3ofHPI ef OjhGf GdHMQGfjs - (3eGLO Hf gGTe Hf Ydj GdMSjfj GdHMQGfj ,CHh Ydj,J (B1022 (3g` s ((3eMeO GdSeGhj s)
(3ChdgG (B:s
(3bGd QMeg Gddg jQKj LOg GdMSjf Hci hdjS Ydj UHQ HeYPhQ ef bO CWqd Ydjg YTQ YGThQ s
(3BNQgG (B:s
(3aCUHMJ efRha GdaDGO cCfeG SbJfj YbGQkG BNQ Gddjd UQNO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B163 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B1s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI HGdfLa (B(1090) s
Keywords: (3GdCOHs